Effect of Risk Management Practices on Production of Seaweed Farming: Evidence from Takalar, South Sulawesi, Indonesia - Fariyanti, Anna; Utami, Anisa Dwi; Yanamisra, Alfira; Miranda , Vanesha; Muflikh, Yanti Nuraeni; Yanuar, Rahmat; Suprehatin, Suprehatin (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
Despite the potential to grow and earn more profit through export, the seaweed sector is dealing with several difficulties, including challenges in the production faced by smallholder farmers. Farmers have managed their seaweed farming by implementing several risk management practices. This study examined the effect of farmers’ risk management practices on seaweed production and the determinants of seaweed production risk management practices. This study utilized data from a survey of 100 farmers in Takalar Regency, a key seaweed production area in Indonesia, along with insights from a focus group discussion (FGD) with seaweed experts. A Cobb-Douglas production function and logistic regression were employed. The findings unveiled that seaweed farmers’ risk management practices had positively boosted their seaweed production. The findings also highlighted that such factors as education level, farming experience, farm size, and weather risk influenced the farmers’ practices of dealing with the production risk. Understanding the effect of risk management practices on farm production and the determinants of production risk management practices could assist policymakers in designing effective policies and farmers in being more innovative in their coping strategies to mitigate production risk, leading to improved productivity and income. The prioritized risk management practices for seaweed production focused on diversifying planting locations and harvesting under hot temperatures to mitigate production risks. In contrast, practices such as changing seeds, relocating, and adjusting cultivation methods were also crucial but less widely applied.